Comparison of Edgefile X3-One Curve File Systems and Cold Lateral Condensation-Single Cone Filling Techniques in Monoblocks With Simulated Curved Root Canals - Murat Maden; Deniz Karaosmanoğlu Akin (Current Research in Dental Sciences)
Objective: The present study aimed to compare the effects of EdgeFile X3 and One Curve files on the angle of curvature and the effectiveness of cold lateral condensation and single-cone filling techniques in monoblocks with curved root canals. Methods: One hundred and eight monoblocks were divided into three main groups according to the curvature angle. Main group I had curvature angle of 5° at a distance of 6 mm from the root apex; main group II had curvature angle of 20° at the same distance from the root apex; and main group III had curvature angle of 20° at the same distance and curvature angle of 30° at a distance of 12 mm from the root apex. The main groups were divided into sub and end groups according to the use of Edgefile X3, One Curve, cold lateral condensation and single-cone techniques. Results: With the One Curve, more straightening was observed in the curvature angle of the root canals in main group III. In main group III, there was a significant negative correlation between the change in apical and coronal curvature angles and the gutta-percha ratio and a significant positive correlation with the canal sealer ratio for both techniques. Conclusions: With the Edgefile X3 file system, the shaping process took less time and the angular change was less. It was concluded that the main determinant of higher gutta-percha ratio was the filling technique used and the single-cone filling technique was more successful. Keywords: Transportation, Resin block, EdgeFile X3, One Curve, Single-cone, Cold lateral condensation